A prospective study of incisional surgical site infections in abdominal surgeries in Maheswara Medical College - Patil, Santosh M.; Dharmapuri, Augusty (International Surgery Journal, 2019)
Background: Infections that occur in the wound created by an invasive surgical procedure are generally referred to as surgical site infections (SSIs). SSIs are one of the most important causes of healthcare associated infections (HCAIs), second only to urinary tract infection (UTI) in incidence. Methods: These patients underwent elective surgeries and were followed up for superficial Incisional surgical site infections until complete wound healing occurred or on their discharge from the hospital. The inclusion criteria for superficial Incisional surgical site infections were: infections occurring within 30 days of operation involving only skin or subcutaneous tissue of the incision with purulent drainage, with or without laboratory confirmation from the superficial incision; organisms isolated from an aseptically obtained culture of fluid or tissue from the superficial incision. Infections occurring after 30 days of operation were excluded from the study. Results: The present study revealed 13.15% prevalence of SSI in department of general surgery, Maheswara Medical College, Hyderabad. Among the 3 types, superficial incision SSI was most prevalent followed by deep incisional SSI and finally by organ/space SSI. The surgical procedure most commonly associated with SSI was exploratory laparotomy. An alarming 19.42% of SSI was associated with emergency surgeries as compared to 7.05% of elective surgeries. Conclusions: The consequences of SSIs greatly impact patients and the healthcare systems. Prevention of SSI requires a multifaceted approach targeting pre, intra, and postoperative factors.